Populasi Burung pada Habitat Nipah di Pantai Tiram Kabupaten Padang Pariaman Provinsi Sumatera Barat - Eko Subrata; Gusmardi Indra; Endri Gustami (Universitas Sam Ratulangi, 2023)
Nipah is one of the main species that make up the mangrove ecosystem that can support the survival of birds with the availability of food, resting places, nesting, perching and breeding and shelter for the birds. The activity of calculating the population of bird species is carried out to protect birds from threats and damage to their habitat. Observations were made on January 9, 2022 at Tiram Tapakih Beach, Ulakan Tapakih District, Padang Pariaman Regency, West Sumatra Province using direct counting or the census method along the nipah habitat while counting birds from 10.00 am to 18.00 pm. Based on observations, found 9 species of birds with a total of 36,388 individuals consisting of 5 families. The species most commonly found was Bubulcus ibis, 36,352 species.